Pesticide Usage in Northern Ireland Survey : Report 293 : Northern Ireland Outdoor Vegetable Crops 2019 : A National Statistics Publication.: Report 293 : Northern Ireland Outdoor Vegetable Crops 2019 : A National Statistics Publication. ([2020]) - Lavery, M. K; Jess, S; Kirbas, J.M; Matthews, D; National Statistics,; Northern Ireland., Department for Environment, Food and Rural Affairs,
No abstract available